Copper-Containing Agates of the Avacha Bay (Eastern Kamchatka, Russia) - Galina Palyanova; Evgeny Sidorov; Andrey Borovikov; Yurii Seryotkin (Minerals, 2020)
The copper-containing agates of the Avacha Bay (Eastern Kamchatka, Russia) have been investigated in this study. Optical microscopy, scanning electron microscopy, electron microprobe analysis, X-ray powder diffraction, Raman spectroscopy, and fluid inclusions were used to investigate the samples. It was found that copper mineralization in agates is represented by native copper, copper sulphides (chalcocite, djurleite, digenite, anilite, yarrowite, rarely chalcopyrite) and cuprite. In addition to copper minerals, sphalerite and native silver were also found in the agates. Native copper is localized in a siliceous matrix in the form of inclusions usually less than 100 microns in size—rarely up to 1 mm—forming dendrites and crystals of a cubic system. Copper sulphides are found in the interstices of chalcedony often cementing the marginal parts of spherule aggregates of silica. In addition, they fill the micro veins, which occupy a cross-cutting position with respect to the concentric bands of chalcedony. The idiomorphic appearance of native copper crystals and clear boundaries with the silica matrix suggest their simultaneous crystallization. Copper sulphides, cuprite, and barite micro veins indicate a later deposition. Raman spectroscopy and X-ray powder diffraction results demonstrated that the Avacha Bay agates contained cristobalite in addition to quartz and moganite. The fluid inclusions study shows that the crystalline quartz in the center of the nodule in agates was formed with the participation of solutions containing a very low salt concentration (<0.3 wt.% NaCl equivalent) at the temperature range 110–50 °C and below. The main salt components were CaCl2 and NaCl, with a probable admixture of MgCl2. The copper mineralization in the agates of the Avacha Bay established in the volcanic strata can serve as a direct sign of their metallogenic specialization.